EDUKASI KESEHATAN DAN DIVERSIFIKASI KANGKUNG “MIKASELA” (MIE KANGKUNG SEHAT, ENAK DAN HALAL) DI DESA MONCONGLOE LAPPARA, MAROS - Rahmat Kosman; Sukmawati; A. Hasrawati (Akademi Farmasi Yamasi Makassar, 2025)
The synergism of life fostered together can increase metabolic products that can potentially be utilized for useful purposes for humans, especially in the field of health. Kale plant development is a very popular vegetable. This vegetable is usually made into stir-fry, chili, or fresh vegetables. Kale is also efficacious as an anti-toxin and can treat various health problems. In addition to its good taste, kale also has a high nutritional content. Kale contains vitamins A, B, C, protein, calcium, phosphorus, carotene and sitosterol and mineral ingredients, especially iron, which are useful for the growth and health of the body. The abundant availability of kale and the perishable nature of the product cause the selling price of kale to be low. This results in farmers often suffering losses. This activity was carried out with a direct training method to the target group. The training began with socialization of the benefits of kale, training on how to make healthy, halal and presentation kale noodles, then preparing a follow-up plan. The expected outputs in this activity are 1) The creation of products in the form of noodles made from kale that can be consumed daily; 2) The opening of business opportunities for partner communities; 3) The formation of a community that cares about health; 4) The formation of a frugal society. And to determine the level of understanding, counseling participants were conducted pretest and postest. The results achieved from this activity are the increased knowledge of partners in Moncongloe lappara Village, Maros about the utilization of kale as a healthy and halal noodle base.